Understanding and Overcoming Key Challenges of Agripreneurs in Southern Odisha: A Case Study - Das, Netrananda; Modak, Satarupa; Prusty, Ajay Kumar; Saha, Parnika (Indian Journal of Extension Education, 2025)
The study, conducted during 2023 and 2024, investigates the constraints faced by agripreneurs in Southern Odisha and provides actionable suggestions to address these challenges. Data were collected from 120 agripreneurs across the Gajapati and Rayagada districts using personal interviews and random sampling. The collected data were analysed using the Rank-Based Quotient (RBQ) method to identify and prioritise key barriers. The findings revealed that knowledge and skills constraints ranked highest (66.07), highlighting inadequate technical expertise, lack of awareness, and insufficient training. Financial constraints followed (57.24), emphasising high risk, complex bank loan procedures, and substantial initial capital requirements. Personal and social challenges (53.37) and psychological limitations (49.78) were also identified but ranked lower. The study’s recommendations, supported by word cloud analysis, stress the need for financial support, risk mitigation strategies, access to modern technologies, and expert advice. Suggested interventions include simplifying loan procedures, providing skill development programs, and fostering a supportive entrepreneurial ecosystem. The study addresses barriers to agripreneurship in Southern Odisha and may enhance agripreneurs’ potential, promote sustainable agricultural development and rural economic growth, and provide valuable insights for policymakers and stakeholders by emphasizing skill development and technological integration.